Biblical Principles of Leading and Managing Employees - Winston, Bruce E. (Christian Faith Perspectives in Leadership and Business, 2018)
This book examines the scriptural concepts that apply to leading and managing people. It begins with a chapter that contrasts leaders, managers, and administrators and the roles they each play. The book then presents the seven virtues from the Beatitudes and how these virtues result in leaders and managers' behaviors. The book then reviews the 15 characteristics of what love is and what love is not from the 1 Corinthians 12 passage. The book presents the four modalities of leaders as conveyed in the Ezekiel 1 and 10 chapters, as well as Revelations 4 where Ezekiel and John describe the four faces of the winged beings. The modalities are described in terms of contemporary leaders interacting with employees in the workplace. A chapter follows, based on the Parable of the Vineyard and how leaders should provide a minimum living wage. The book then compares the wife in Proverbs 31 to a good leader/manager in today's contemporary organization. The book ends with an admonition from Ecclesiastes 3:1 about the need for leaders/managers to step away and not meddle when the leader/manager's role is finished. Throughout the book, composite case examples provide practical application of the concepts to contemporary organizations.